DISCUSSION AS ONE OF THE METHODS OF DEVELOPING COMMUNICATION SKILLS IN LEARNING ENGLISH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this article, the main focus today is on the reader, his personality and his own inner world. Therefore, the main goal of a modern teacher is the choice of methods and forms of Organization of educational activities students, optimally corresponding to the established goal of personal development. In recent years, the question of the use of new information technologies in schools has been increasingly raised.